Education Through Providing Learning Motivation and Reproductive Health Information Sources in Forming Adolescent Sexual Behavior - Nurianti, Irma; Simargolang, Inda Andini (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2024)
The issue of adolescent reproduction is now widespread news that is spreading in developing countries. As many as 21 million teenage girls aged 15–19 years are pregnant each year, of which 49% are unexpected pregnancies. Reproductive health is important in realizing the welfare of adolescents now and in the future. Sexual behavior that can be addressed well will affect the reproductive health of adolescents. By providing appropriate sources of information about reproductive health, good sexual behavior will be formed. Learning motivation plays a role in developing students' academic and non-academic values ??so that they can be wise in understanding sexual behavior. Educational activities through counseling will increase the learning motivation of PkM participants and provide the latest sources of information regarding reproductive health which will later be useful in establishing good sexual behavior. The stages in implementing PkM include question and answer, pre-test and post-test, delivery of material, discussion, and evaluation of activities. The PkM participants were 50 class XI students at SMK Al-wasiyah 9 Perbaungan. Sexual behavior can influence students' motivation to participate in learning. Sources of information about reproductive health through the WHO, CDC, and Planned Parenthood websites help participants develop good sexual behavior. Through this educational activity, PkM participants have increased their knowledge and motivation to learn, as evidenced by an average post-test score of 85.2 where the previous average pre-test score was 65.8.